2002
DOI: 10.1007/s005350200002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of homeobox gene CDX2 precedes that of CDX1 during the progression of intestinal metaplasia

Abstract: The expression of CDX2 precedes those of CDX1, sucrase-isomaltase, other intestine-specific genes (human defensin-5, alkaline phosphatase), and MUC2 during the progression of intestinal metaplasia. These findings imply that the expression of CDX2 may trigger the initiation and development of intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
115
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 28 publications
7
115
0
6
Order By: Relevance
“…Functional studies have already shown CDX2 could regulate many intestine-specific gene transcription in vivo. Such like intestinal-type alkaline phosphatase (ALP); the well characterized brushborder enzyme, sucrase-isomaltase (SI), human defensin-5 (HD), and mucus-secreting goblet cell-mucin marker (MUC2) (Eda et al, 2002;Guo et al, 2004;Weimann et al, 2010). These genes control the differentiation of the IM of gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies have already shown CDX2 could regulate many intestine-specific gene transcription in vivo. Such like intestinal-type alkaline phosphatase (ALP); the well characterized brushborder enzyme, sucrase-isomaltase (SI), human defensin-5 (HD), and mucus-secreting goblet cell-mucin marker (MUC2) (Eda et al, 2002;Guo et al, 2004;Weimann et al, 2010). These genes control the differentiation of the IM of gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6]8 Ectopic expression of CDX2 is known to induce intestinal phenotypes such as MUC2 expression in Barrett's esophagus, and bile acid or chronic acid exposure was speculated to induce CDX2 expression in esophageal keratinocytes. 8,29 Inflammatory cytokines and infection may also induce CDX2 and then MUC2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…8,29 Inflammatory cytokines and infection may also induce CDX2 and then MUC2 expression. 2,[4][5][6] For example, CDX2 expression was reportedly upregulated in cultured epithelial cells when they were infected with bacteria, and interactions of TLR with microbial components are involved in the regulation of MUC expression. [30][31][32][33][34][35] Therefore, bacterial components in bile may induce CDX2 expression and then aberrant MUC2 expression in the ducts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations